2021
DOI: 10.3390/antiox10091483
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Regulation of Biomolecular Condensates in Neurodegenerative Disorders

Abstract: Biomolecular condensates are membraneless organelles (MLOs) that form dynamic, chemically distinct subcellular compartments organizing macromolecules such as proteins, RNA, and DNA in unicellular prokaryotic bacteria and complex eukaryotic cells. Separated from surrounding environments, MLOs in the nucleoplasm, cytoplasm, and mitochondria assemble by liquid–liquid phase separation (LLPS) into transient, non-static, liquid-like droplets that regulate essential molecular functions. LLPS is primarily controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 1,138 publications
(1,573 reference statements)
0
19
0
Order By: Relevance
“…Conversely, the level of CD4+ T cells—regarded as a biomarker of protective immunity [ 285 ]—is usually significantly reduced in adults with severe or critical COVID-19 compared to healthy controls [ 286 ]. Melatonin protects both mitochondrial and extracellular ATP production by maintaining curvature and ensuring structural integrity of lipid domains where ATP synthases and ATPases are located [ 287 ]. The ability of SARS-CoV-2 to disrupt ATP synthases, and its efficacy in modulating mitochondrial dynamics and metabolism to evade host immune response, enhance replication, and establish viral persistence may be attenuated by the well-timed presence and/or application of adequate melatonin [ 288 ].…”
Section: Melatonin Is An Ancient Molecule That Can Regulate Virus Pha...mentioning
confidence: 99%
“…Conversely, the level of CD4+ T cells—regarded as a biomarker of protective immunity [ 285 ]—is usually significantly reduced in adults with severe or critical COVID-19 compared to healthy controls [ 286 ]. Melatonin protects both mitochondrial and extracellular ATP production by maintaining curvature and ensuring structural integrity of lipid domains where ATP synthases and ATPases are located [ 287 ]. The ability of SARS-CoV-2 to disrupt ATP synthases, and its efficacy in modulating mitochondrial dynamics and metabolism to evade host immune response, enhance replication, and establish viral persistence may be attenuated by the well-timed presence and/or application of adequate melatonin [ 288 ].…”
Section: Melatonin Is An Ancient Molecule That Can Regulate Virus Pha...mentioning
confidence: 99%
“…In previous studies, pathway analyses have predicted the potential effect of m6A methylation RNA in AD, and the high-throughput sequencing of m6A RNA methylation alterations in AD and C57BL/6 mice was also verified this association [ 52 , 53 ]. Besides, m6A controls key gene expression in AD- related pathways, which indicates that m6A renders its essential roles in aging and neurodegenerative diseases [ 54 ]. In our study, we found that IGF2BP2, as a m6A reader, increased in AD patients than in normal people, which might indicate a potential relationship with the occurrence of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, under physiological conditions, Cu 2+ bound to full-length, uncleaved PrP can induce misfolding that increases seeding, which serves as templates for aggregation [ 300 , 301 ]. Melatonin is not only a potent antioxidant capable of chelating copper and modulating ROS-dependent prion cleavage, but is also proposed to be an important regulator of phase separation [ 125 ].…”
Section: Liquid–liquid Phase Separation May Regulate Prion Conversion...mentioning
confidence: 99%
“…Melatonin may efficiently mediate important PTMs that regulate proteins which can form physiological condensates or pathological prion-like aggregates due to its ability to protect mitochondrial and cytoplasmic ATP levels and maintain requisite RNA concentration, which not only ensure proper formation and dissolution of condensates [ 125 ] but possibly also modulate reentrant phase transitions that are important biochemical timekeeping RNA-dependent transformations where increased RNA dissolves condensates to return to an identical or macroscopically similar state before the phase transition [ 324 ]. Since prion targeting of lipid rafts [ 272 , 325 , 326 ] can affect membrane signaling [ 327 , 328 ] and lipid composition [ 329 ], the role of melatonin in the prevention of lipid peroxidation, modification of lipid hydrocarbon chain to promote phase separation in ternary membrane models [ 330 , 331 ], stabilizing lipid liquid ordered (L o ) to liquid disordered (L d ) phase separation over a range of temperatures [ 332 ], and displacing cholesterol in competitive binding to lipid molecules [ 330 ] provides additional insight into the complex relationship between melatonin and prion physiological and potential pathological conversion mediated by phase separation and associated processes.…”
Section: Liquid–liquid Phase Separation May Regulate Prion Conversion...mentioning
confidence: 99%
See 1 more Smart Citation